Electric Vehicles and Urban Noise Control Policies - MAFFEI, Luigi; MASULLO, Massimiliano (Archives of Acoustics, 2014)
Limited Traffic Zone (LTZ) is a planning strategy that is more and more adopted by municipalities in Europe to improve their environmental conditions. It consists in the prohibition for traditional vehicles to circulate in specific areas. Although the main aim is to tackle air pollution problems, positive effects are registered in terms of reduction of noise annoyance and in terms of improved “quality of life” if specific conditions are respected. On the other side under the drive of the global market, the number of circulating electric vehicles in urban sites is also increasing. In the next years we expect to experience a new and not well-known urban soundscape.In this paper is presented an overview of recent urban projects and policies that deal with noise control and how these experiences will match into the next years with the sound characteristics of new electric vehicles for private and public transportation.